YOUR SERVANT JESUS WHOM YOU ANOINTED (ACTS 4,27) - Kilgallen, John J. (Revue biblique, 1998)
The Christians' prayer of Acts 4,24-30 clearly identifies Jesus as Lord by identifying him as such through use of Psalm 2,1-2. The prayer further identifies the Lord Jesus as Messiah. This article studies Luke 4,18 (vis-a-vis 3,21-22) and Acts 10,38 for their contribution to the meaning of the Anointed One. The article draws a clear distinction between the mission of the Anointed Lord and his paschal experience, in accord with these loci in Luke 4 and Acts 10. La prière des chrétiens en Actes 4,24-30 désigne Jésus comme Seigneur en l'identifiant comme tel par le Ps. 2,1-2. La prière, de plus, désigne Jésus comme Messie. L'article étudie Luc 4,18 (face à 3,21-22) et Actes 10,38 pour leur apport à la signification de l'Oint. On trace une distinction entre la mission du Seigneur Oint et son expérience pascale, en accord avec ces passages de Luc 4 et Actes 10.